Thermal plasticity and microevolution enhance establishment success and persistence of a water hyacinth biological control agent. Issue 7 (22nd July 2019) - Griffith, Tamzin C.; Paterson, Iain D.; Owen, Candice A.; Coetzee, Julie A.
Abstract: Aspects of the thermal physiology of the water hyacinth biological control agent Eccritotarsus catarinensis Carvalho (Hemiptera: Miridae) have been extensively investigated over the past 20 years to understand and improve post‐release establishment in the field. Thermal physiology studies predicted that the agent would not establish at a number of cold sites in South Africa, where it has nonetheless subsequently established and thrived. Recently, studies have begun to incorporate the plastic nature of insect thermal physiology into models of agent establishment. This study determined whether season and locality influenced the thermal physiology of two field populations of E. catarinensis, one collected from the hottest site where the agent has established in South Africa, and one from the coldest site. The thermal physiology of E. catarinensis was significantly influenced by season and site, demonstrating a degree of phenotypic plasticity, and that some post‐release local adaptation to climatic conditions has occurred through microevolution. We then determined whether cold acclimation under laboratory conditions was possible. Successfully cold‐acclimated E. catarinensis had a significantly lower critical thermal minimum (CTmin ) compared to the field cold‐acclimated population. This suggests that cold acclimation of agents could be conducted in the laboratory before future releases to improve their cold tolerance, thereby increasing their chance of establishment at cold sites and allowing further adaptation to colder climates to occur in the field. Although the thermal tolerance of E. catarinensis is limited by local adaptations to climatic conditions in the native range, the plastic nature of the insect's thermal physiology has allowed it to survive in the very different climatic conditions of the introduced range, and there has been some adaptive change to the insect's thermal tolerance since establishment. This study highlights the importance of plasticity and microevolutionary processes in the success of biological control agents under the novel climatic conditions in the introduced range. Abstract : A classical biological weed control agent, Eccritotarsus catarinensis (Hemiptera: Miridae), established at sites that were predicted to be outside of the thermal tolerance of the species. Phenotypic plasticity as well as microevolution since its release have resulted in changes to its thermal physiology. This study highlights the importance of plasticity and microevolutionary processes in the success of biological control agents under the novel climatic conditions in the introduced range.